Cultivar and growth phases – the factors affecting antioxidant activity of buckwheat (Fagopyrum esculentum Moench.) - Janette MUSILOVÁ; Jaromír LACHMAN; Judita BYSTRICKÁ; Alena VOLLMANNOVÁ; Iveta ČIČOVÁ; Mária TIMORACKÁ (Acta Agriculturae Slovenica)
The aim of this study was to assess the influence of cultivar and growth phase on the antioxidant activity (AOA) changes in common buckwheat (Fagopyrum esculentum Moench), as well as the its distribution in different plant parts. During 4 growth phases (GP) (buds formation - I, beginning of flowering - II, full flowering - III, full maturity - IV) stems, leaves, flowers, seeds were collected sequentially from 6 buckwheat cultivars – ‘Pyra’, ‘Spacinska’, ‘Kasho’, ‘Jana C1’, ‘Hrusowska’, ‘Emka’. The highest values of AOA were measured in flowers (GP III) in ‘Jana C1’ (93.17%) and the lowest value in stems (GP I) in ‘Spacinska’ (46.09%). The highest increase of AOA was observed in GP IV in stems in ‘Pyra’. Differences were compared for statistical significance at the level P < 0.05.